Academic Hardiness terhadap Career Decision Self-Efficacy Siswa SMA di Masa Pandemi COVID-19 - Fatma Nuraqmarina (Jurnal Ilmiah Psikologi MIND SET, 2021)
The pandemic situation due to the COVID-19 outbreak that is happening in Indonesia is causing a completely changing situation, thus making high school students experience confusion in choosing a career after graduating from school. This problem can be solved if students have academic hardiness so that they contribute to career decision self-efficacy (CDSE). This study aims to determine the relationship between academic hardiness and career decision self-efficacy. This research was conducted on 362 high school students (91 male students, 271 female students) in the areas of Jakarta, Depok, Tangerang, Bogor and Bekasi. The high school students consisted of 252 high school students, 32 vocational students, and 78 MA students. The results showed that there was a positive and significant relationship between academic hardiness and students' career decision self-efficacy. The stronger the student's academic hardiness, the stronger the student's career decision self-efficacy (r = 0.445 and p = 0.000). Based on the results of this study, career counselors in schools can help high school students (SMA, SMK and MA) improve career decision self-efficacy by teaching academic hardiness skills.